Proteomic Characterization Reveals That MMP‐3 Correlates With Bronchiolitis Obliterans Syndrome Following Allogeneic Hematopoietic Cell and Lung Transplantation. Issue 8 (14th March 2016) - Liu, X.; Yue, Z.; Yu, J.; Daguindau, E.; Kushekhar, K.; Zhang, Q.; Ogata, Y.; Gafken, P. R.; Inamoto, Y.; Gracon, A.; Wilkes, D. S.; Hansen, J. A.; et al.
Abstract : Improved diagnostic methods are needed for bronchiolitis obliterans syndrome (BOS), a serious complication after allogeneic hematopoietic cell transplantation (HCT) and lung transplantation. For protein candidate discovery, we compared plasma pools from HCT transplantation recipients with BOS at onset (n = 12), pulmonary infection (n = 16), chronic graft‐versus‐host disease without pulmonary involvement (n = 15) and no chronic complications after HCT (n = 15). Pools were labeled with different tags (isobaric tags for relative and absolute quantification), and two software tools identified differentially expressed proteins (≥1.5‐fold change). Candidate proteins were further selected using a six‐step computational biology approach. The diagnostic value of the lead candidate, matrix metalloproteinase 3 (MMP3), was evaluated by enzyme‐linked immunosorbent assay in plasma of a verification cohort (n = 112) with and without BOS following HCT (n = 76) or lung transplantation (n = 36). MMP3 plasma concentrations differed significantly between patients with and without BOS (area under the receiver operating characteristic curve 0.77). Consequently, MMP3 represents a potential noninvasive blood test for diagnosis of BOS. Abstract : By combining discovery proteomics, computational biology, and enzyme‐linked immunosorbent assay validation, this study discovers that the plasma concentration of MMP‐3 is significantly elevated in patients with bronchiolitis obliterans syndrome following allogeneic hematopoietic cell and lung transplantation compared with those without the syndrome.